Performance spaces in Lumban Silintong area. Issue 1 (May 2020) - Siagian, M; Sitorus, R
Abstract: Lumban Silintong, Balige which is located in the bank of Lake Toba has changed very rapidly after the Central Government of Indonesia set Lake Toba as one of 10 major tourism destination in the country and established Badan Otorita Danau Toba (BODT) was in 2016. The beach which was a public space where all the community from the area and visitors from outside get access to the lake for free, and enchant beautiful lake view without limitation. Today it becomes a commercial space. The owners of money built currently 18 cafes along this beach. The area become space for private activities which characterized by modernity which are forming space gaining maximum profit. The 24-hour live cafes do not stop having eliminated the daily activities of local people and become commercial activities for the sake of café owners. District governments that are unable to enforce regulations on development along the beach cause the appearance the beach is not controlled. With mixed research methods, this study was done with observations, data collecting, photo taking that local space along the beach of Lumban Silintong which was used to be experienced and used by the public for free, now become commodities with modern concepts.